Soybean tolerance to defoliation at the vegetative and reproductive stages as a function of water restriction - Leolato L.S.* (2022)
© 2022, Eduem - Editora da Universidade Estadual de Maringa. All rights reserved.Water deficiency reduces leaf expansion and photosynthetic efficiency, potentially reducing the ability to withstand leaf area (LA) loss. This study aimed to evaluate the effects of water restriction on soybean tolerance to defoliation in the vegetative and reproductive periods of development. Two experiments were conducted in a greenhouse located in Lages, Santa Catarina State Brazil, during the 2017/2018 growing season. Cultivar NA 5909 RG was subjected to three WR levels (none, moderate, and severe) and five defoliation levels (0, 17, 33, 50, and 67%). Defoliation occurred at the V6 stage in the first experiment and R3 in the second. WR occurred for 7 days after defoliation. LA at R2 and R5 after defoliation at V6 and R3 decreased by 27.5 and 64.6%, respectively, regardless of WR. LA between V6 and R2 was not influenced by WR or defoliation. Moderate or severe WR reduced plant ability to recover LA between R3 and R5. Severe WR decreased grain production by 22.2% in the vegetative period and 21.2% per plant in the reproductive period compared to that of the control, regardless of defoliation. The highest defoliation level reduced grain production per plant by 24.7 and 24.3% relative to the control at stages V6 and R3, respectively, regardless of WR. WR imposed at the vegetative and reproductive stages did not increase defoliation sensitivity.